Embracing Conceptualizations of English Language Teacher Education From a Complexity Perspective - Martha Garcia-Chamorro; Nayibe Rosado-Mendinueta (Universidad Nacional de Colombia, 2021)
Current conceptualizations of foreign language teacher education fail to represent the complexity of such education. This reflection highlights the need to embrace English language teacher education from a complex perspective. To explain this position, we define complex systems and complexity principles through examples of interconnected components of teacher education. Then, we trace emergent conceptualizations from theory and governmental documents that resonate with a complexity perspective. We suggest that efforts in this direction may better prepare prospective English teachers to face challenging realities in educational settings and will eventually improve students' learning, an outcome every stakeholder is aiming at.